2016
DOI: 10.3389/fped.2016.00054
|View full text |Cite
|
Sign up to set email alerts
|

The BULT Method for Pediatric Minilaparoscopic Pyeloplasty in Infants: Technique and Results

Abstract: We reviewed retrospectively the results of transperitoneal minilaparoscopic pyeloplasty in children younger than 2 years. The surgical technique utilized as well as the retrograde placement of the stent is described in detail. Twenty-four consecutive children with a mean age of 7.9 months (range 1-23), a mean weight of 7.4 kg (range 4-12), and a mean follow-up of 18 months (range 3-59) are included. Preoperative grade of dilatation was 3.8 (SFU scale) and postoperatively improved to 1.5. The AP diameter of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…Late complications rate (two patients −3.4%) are similar to the literature (24, 25, 27). Malrotated kidneys remain a challenge because of the unexpected position and technical difficulties, like in 1 of our cases.…”
Section: Discussionsupporting
confidence: 88%
“…Late complications rate (two patients −3.4%) are similar to the literature (24, 25, 27). Malrotated kidneys remain a challenge because of the unexpected position and technical difficulties, like in 1 of our cases.…”
Section: Discussionsupporting
confidence: 88%
“…Although most series report longer operative time in LP, (mean 155-240min) (3,8,11,16) we had spent a mean of 107min., which may be near the open procedures time. Previous adult experience, same team, routine and focusing on simplifying every step certainly play a role in the operative time.…”
Section: Discussionmentioning
confidence: 83%
“…Since then, a few pediatric large se- Conversion to open procedure 0 (8). However, while early series had reported anastomotic stenosis in babies (9,10), subsequent studies demonstrated feasibility irrespective of patient age and weight (6,7,(11)(12)(13). LP has been thought to be a technically challenging procedure in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the operable space in a children’s body is small for laparoscopy, performing precise anastomotic suturing is restricted and the duration of operation is longer than OP, especially in LDP by retroperitoneal approach [6, 7]. Furthermore, it is easy to cause accidental damage to the surrounding tissues, resulting in bleeding and an increased risk for anastomotic stenosis for LDP in children [8].…”
Section: Introductionmentioning
confidence: 99%